2021
DOI: 10.1371/journal.pone.0245556
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in susceptibility, severity, and outcomes of coronavirus disease 2019: Cross-sectional analysis from a diverse US metropolitan area

Abstract: Introduction Sex is increasingly recognized as an important factor in the epidemiology and outcome of many diseases. This also appears to hold for coronavirus disease 2019 (COVID-19). Evidence from China and Europe has suggested that mortality from COVID-19 infection is higher in men than women, but evidence from US populations is lacking. Utilizing data from a large healthcare provider, we determined if males, as compared to females have a higher likelihood of SARS-CoV-2 susceptibility, and if among the hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
125
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(188 citation statements)
references
References 18 publications
29
125
4
1
Order By: Relevance
“…The presence of multiple comorbidities has been associated with a worse prognosis and higher mortality rate since the start of the COVID-19 pandemic [28]. As also reported by the most recent publications [17,29], we con rmed that cardiovascular diseases and endocrinopathies, especially diabetes mellitus, are the most frequent comorbidities in patients admitted to our hospital, even though with no sex differences. This is in contrast with some recently published data obtained in 340 Italian and Spanish patients in whom cardiovascular disorders were more frequent in males [18].…”
Section: Discussionsupporting
confidence: 82%
“…The presence of multiple comorbidities has been associated with a worse prognosis and higher mortality rate since the start of the COVID-19 pandemic [28]. As also reported by the most recent publications [17,29], we con rmed that cardiovascular diseases and endocrinopathies, especially diabetes mellitus, are the most frequent comorbidities in patients admitted to our hospital, even though with no sex differences. This is in contrast with some recently published data obtained in 340 Italian and Spanish patients in whom cardiovascular disorders were more frequent in males [18].…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies showed that AKI was more common in male patients compared to females (Su et al, 2020;Vahidy et al, 2021). However, our study found that the incidence of AKI was higher in females than males.…”
Section: Discussioncontrasting
confidence: 77%
“…These data contrast with the presence of severe infection in 80% of Conv and higher frequency of males. The observed sex distribution is consistent with previous findings suggesting females exhibit robust T-cell responses and are less prone to severe SARS-CoV-2 infection and death than males (Takahashi et al, 2020;Jin et al, 2020;Vahidy et al, 2021). No significant differences in age distribution between NSC and Conv were found excluding age as one of the factors accounting for the differences in disease severity observed.…”
Section: Discussionsupporting
confidence: 91%